Late Archean to Early Paleoproterozoic global tectonics, environmental change and the rise of atmospheric oxygen - Barley, M.; Bekker, A.; Krapez, Bryan (Elsevier Science BV, 2005)
Analysis of the tectonostratigraphic records of Late Archean to Early Paleoproterozoic terranes indicates linkage between global tectonics, changing sea levels and environmental conditions. A Late Archean tectonic cycle started at ~2.78 Ga involving the breakup of a pre-existing continent (Vaalbara) and the most prodigious period of generation and preservation of juvenile continental crust recorded in Earth history during a period of plume breakout (~2.72 to 2.65 Ga) accompanied by high sea levels. During this period, cratons formed by accretion of granitoid–greenstone terranes at convergent margins started to aggregate into larger continents (e.g. Kenorland). Lower sea levels between ~2.65 and 2.55 Ga were followed by a second (~2.51 to 2.45 Ga) period of plume breakout resulting in a global peak in magmatism, high sea levels and deposition of banded iron formations (BIF) on the trailing margins of the Pilbara and Kaapvaal cratons. Cratons in South Australia, Antarctica, India, and China record convergent margin magmatism, orogeny and high-grade metamorphism between 2.56 and 2.42 Ga. Continued aggregation of continental fragments (e.g. amalgamation of Indian cratons) may have formed the Earth’s first supercontinent by ~2.4 Ga with a return to low sea levels and relative tectonic quiescence before the supercontinent started to breakup from ~2.32 Ga. Although oxygenic photosynthesis had evolved by 2.71 Ga, the irreversible rise of atmospheric O2 to N105 PAL appears to have occurred between 2.47 and 2.40 Ga following the second plume breakout and coinciding with a decline in BIF deposition and the maximum extent of the supercontinent suggesting dynamic linkage between tectonics and both the sources and sinks of oxygen. Periods of plume breakout (2.72 to 2.65 Ga and 2.51 to 2.45 Ga) would have limited ocean productivity and the rate of photosynthesis and also enhanced the reduced conditions typical of the Archean biosphere, as well as the greenhouse gas contents of the atmosphere necessary to maintain temperate conditions. This suggests that either an increase in the oxidation state of volcanic gasses during the second plume breakout, or a decreased flux of reduced gasses following plume breakout, coupled with the filling of crustal oxygen sinks and possibly also an increase in ocean productivity and the rate of photosynthesis resulted in the global flux of reduced gasses falling below oxygen production leading to a rise of atmospheric O2 accompanied by loss of the CH4-rich greenhouse atmosphere resulting in the Earth’s first widespread glaciation. Detrital pyrite and uraninite in 2.45 to 2.40 Ga sediments suggests that terrestrial surface environments were not yet extensively oxidized. The oldest evidence of extensive oxidative weathering is associated with 2.32 to 2.22 Ga glacial deposits and breakup of the supercontinent.